(untitled) (Global Journal of Management and Business Research, 2013)
The effect of CEO entrenchment has often been attached to the company owners wealth measured by financial performance. CEOs are more concerned about coalition members, and recognized the importance of integrating stakeholders into the evaluation system of managerial performance. In this paper, we focus on the evolution of governance systems by integrating stakeholders’ perspective. We illustrate the crossing from the "shareholder" approach to "partnership" approach as part of the activism of managers. Based on some managerial performance ratios as input, our approach is to use a combination of rough set theory, the genetic algorithm and support vector machines to predict whether satisfaction can be a factor that promotes CEO entrenchment. From a sample of 45 Tunisian companies listed during the year period 2008, we evaluate the stakeholders’ influence on the CEO entrenchment strategy. The proposed approach shows that a CEO who cares about his en-trenchment, can provide very favorable conditions to em-ployees and customers who contribute to reduce his risk of being dismissed, to overlap his term of office and even exceed his retirement age.